ROLES AND FUNCTION ON REVITALIZATION OF EDUCATIONAL BOARDS IN EAST JAVA PROVINCE: HERMENEUTIC STUDY OF JURGEN HABERMAS, INDONESIA - Bonaventura Suprapto; Pribadiyono Pribadiyono; Akhmad Riduwan (AIBPM Publisher, 2019)
This study aims to analyze the managerial roles of Educational Boards in East Java Province, Indonesia. In particular, this concerns on five aspects, i.e. operational activities, human resources, organizational roles and functions, and facilities in the organization. In the management of educational council, there are many experts in their fields; however, its internal problem is in regard with human resources. The unhealthy organizational structures in determining organizational funds and facilities are also obstacles that need to be addressed to realize the educational council as an independent organization due to the law. Thus, this study argues that the educational boards in East Java Province needs to be revitalized owing to the autonomous principles of education. This relates to the democratization of education, involving conjoint actions and communication between the government and the community to reach the educational consensus.